Optimization of Delivery in Pregnant Women After in Vitro Fertilization - Aziza Rakhmatilloyevna , Yunusova (Research Journal of Trauma and Disability Studies, 2024)
The woman is over 35 years old. 35 years and more is a very important age for having children. During this period, many already have chronic or hereditary diseases that complicate the pregnancy process. These include hypertension, diseases of the kidneys, liver and other important organs. The problem of excess weight due to a sedentary lifestyle and improper diet is also relevant. For these reasons, the risk of developing spontaneous abortion, placenta previa, preeclampsia or diabetes mellitus increases;